Development of Flipbook Based E-Books as Teaching Materials for Biography Texts at SMK Kesehatan Cianjur - Hasanah, Aan; Mulyanti, Sri; Adawiyah, Aprilla; Fatimatul Munsi, Mia; Soleha, Maya; Nurfajrin Ningsih, Dinni (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Education plays a strategic role in enhancing personal quality and national development. This research aims to develop flipbook-based electronic books (e-books) for biographical text instruction targeted at grade X students of vocational high schools. The study employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Results from expert validation indicated that the e-book was highly feasible in terms of material content (mean score = 5.0), feasible in media design (mean score = 4.1), and moderately feasible in linguistic aspects (mean score = 3.2). Student response questionnaires (n=25) revealed positive reception with an overall mean score of 3.96, particularly in language comprehension (mean = 4.32) and visual engagement (mean = 3.96). The flipbook-based e-book effectively facilitated students' understanding of biographical texts through contextual examples, interactive features, and structured scaffolding based on the Genre-Based Approach. This digital teaching material demonstrates potential for enhancing student engagement and writing competency in vocational education contexts.